Fatigue and wear behaviour of zirconia materials. (October 2020) - Rosentritt, Martin; Preis, Verena; Behr, Michael; Strasser, Thomas
Abstract: Objectives: Comparison of in-vitro fatigue and wear performance of 3Y-, 4Y-, 5Y-TZP and lithiumdisilicate ceramic, multilayer/monolayer 4Y-TZP and variation of wall thickness at 5Y-TZP. Method and materials: Crowns (n = 96; 6 groups à 16) were made of 3Y-TZP-LA, 4Y-TZP (multilayer and monolayer), 5Y-TZP (0, 5mm/1 mm wall thickness) and lithiumdisilicate. 8 per group were stored in water (24hrs), 8 underwent TCML (1.200.000 × 50N; 2x3000x5°/55 °C; H2 O, 2min cycle). Fracture force was determined by static loading (v = 1 mm/min, steel sphere with tin foil, diameter = 12 mm). Pin-on-block wear test was performed (steatite antagonist d = 3 mm; 50N, 120, 000 cycles, 1.2Hz, lateral motion: 1 mm, antagonist lift: 1 mm, n = 8). Roughness, wear depth [μm] and antagonist wear were determined (3-D-laser-microscope, KJ3D, Keyence, J). Statistics: one-way-ANOVA; Bonferroni-post-hoc-test; α = 0.05. Results: Fracture forces varied between 1211N (5Y, TCML) and 3952N (4Y-Mult, TCML). Individual significant differences (p ≤ 0.025) were found between materials. Increase of wall thickness (5Y; 0.5 mm/1.0 mm) lead to a non-significant (p ≥ 0.442) increase of fracture force. 4Y and 4Y-multilayer zirconia showed no significantly different (p ≥ 0.073) fracture forces. Zirconia mean wear (3Y:10.0 ± 3.9 μm, 4Y:19.8 ± 3.8 μm, 5Y:10.9 ± 6.8 μm) was not significantly (p = 1.000) different. Lithiumdisilicate ceramic (149.3 ± 45.4 μm) and human enamel (434.2 ± 131.3 μm) provided significantly (p ≤ 0.002) higher wear. Antagonistic wear against lithiumdisilicate (17.5 ± 3.9%) and human enamel (6.7 ± 3.0%) was significantly (p ≤ 0.007) lower than against zirconia (4Y:31.9 ± 8.0% - 5Y:27.6 ± 5.8%). Conclusion: Fracture force of 5Y-TZP differs from 4- or 3-Y-TZP. Mechanical characteristics and dimensional requirement of 5Y-TZP are comparable to lithiumdisilicate. Mono- or multilayer 4Y-TZP provided comparable fracture forces. Wear was comparable between zirconia systems and lower in comparison to lithiumdisilicate or enamel. Highlights: Fracture force of 5Y-TZP differs from 4- or 3-Y-TZP and is comparable to LS2 . 3Y-TZP, 4Y-TZP and 5Y-TZP zirconia systems show comparable wear behaviour. Mono- and multilayer 4Y-TZP provide comparable fracture forces.